Urgensi Orang Tua dalam Pembelajaran Daring di Masa Pandemi Covid-19 bagi Siswa RA: The Urgency of Parents in Online Learning During the Covid-19 Pandemic for Students RA - Ulfa, Risa Alfiyah; Asfahani, Asfahani; Aini, Nurul (Absorbent Mind, 2021)
There are many methods that can be implemented to continue learning even in the state of the Covid-19 pandemic, one of which is learning with an online system, the role of parents is very important so that it can be said to be a benchmark in the success of learning in this pandemic. This research uses qualitative methods with data collection techniques in the form of interviews, observation and documentation. This study uses data analysis techniques with reduction, presentation and drawing conclusions. Based on the results of data analysis, it can be concluded that (1) During the Covid-19 pandemic, learning at RA Muslimat NU 072 Lembah continued using an online system, (2) In this learning system the role of parents was needed by children, (3) There are various obstacles that parents feel when assisting their children in the learning process with an online system.